The expression of survivin in irreversible pulmonary arterial hypertension rats and its value in evaluating the reversibility of pulmonary arterial hypertension secondary to congenital heart disease. (August 2019) - Li, Gang; Zhang, Han; Zhao, Lei; Zhang, Yaozhong; Yan, Daole; Liu, Yinglong; Su, Junwu; Fan, Xiangming
The reversibility of pulmonary arterial hypertension (PAH) determines the operability of congenital heart disease (CHD) complicating with PAH, but it lacks a method for evaluating the reversibility. The current study aims to investigate the serum survivin level in irreversible PAH rats and to explore its potential as a biomarker for evaluating the reversibility of PAH in CHD patients. Irreversible PAH rats were characterized by prominent obstructive lesions resulting from the intimal formation, which was associated with decreased apoptosis and increased survivin expression, while reversible PAH rats were featured by medial hypertrophy resulting in mild occlusion, with increased apoptosis and unchanged survivin expression. In addition, the serum survivin was significantly increased in irreversible PAH rats when compared to both reversible PAH and control rats, and a positive correlation of serum survivin with survivin expression in the lung was confirmed. Third, the preoperative serum survivin was significantly higher in patients with irreversible CHD-PAH than in these with reversible CHD-PAH, and significant correlations between the serum survivin and BNP, preoperative pulmonary vascular resistance index, and postoperative mean pulmonary arterial pressure were also identified. In conclusion, the increased survivin level is a feature of irreversible PAH and the serum survivin represents a candidate biomarker reflecting the operability of CHD-PAH patients.